Indispensáveis Exemplares: a importância dos impressos na instrução pública (Minas Gerais, 1827 1854) - Raquel Menezes Pacheco (2014)
This Master's thesis has been developed through dialogue about research fields of the education history and the books and reading history. It was intended to identify the presence of some printed material in classes focused on the elementary education in the province of Minas Gerais between the years 1827 and 1854. This period is defined by the Law of October 15, 1827, first imperial law that had education as an object, and Regulation n. January 28, 1854, that would reorganize the public education in Minas Gerais. In addition, it was intended to analyze the representations construction about these materials by teachers, delegates from literary circles, provincial presidents and other subjects related to the media and to the political, literary and philanthropic societies, which became created in the period. What were the printed materials that designed / printed or not for schools, came into the hands of teachers and some of them, in the hands of students? How was the print related to the content that should be taught and to the teaching methods in the legislation? Which subjects and locations constituted what we call "printed circuit"? What are the possible reasons for the choice of some printed materials over others? It was attempted to answer these questions by crossing various manuscript and printed sources, such as legislation of the period, correspondence related to the province of Minas Gerais presidency, provincial presidency ordinances to the delegates of literary circles and journal articles from the O Universal (Ouro Preto, 1825-1842) and Jornal da Sociedade Promotora da Instrucção Publica (Ouro Preto, 1832-1834). As a conceptual support, were elected, fundamentally, Roger Chartier and Robert Darnton. Practices that indicate the importance assumed by the print materials in the schooling process in the province of Minas Gerais, in the second quarter of the nineteenth century, were identified. They have become fundamental elements that facilitated, or not, the ownership of teaching methods; led teaching certain content; were involved in a complex dynamic covering trade practices. Despite remaining gaps in this research, it is believed that it has contributed to the expansion of knowledge about the use of printed materials in the schooling process in the first half of the nineteenth century, in the province of Minas Gerais.